Charge-Discharge Performance of Rechargeable Organic-Magnesium Batteries Using Glyme-Based Electrolytes. (20th November 2015) - Senoh, Hiroshi; Sakaebe, Hikari; Tokiwa, Haruki; Uchida, Makoto; Sano, Hikaru; Yao, Masaru; Kiyobayashi, Tetsu
Abstract : Rechargeable batteries composed of metallic Mg negative electrode, glyme-based electrolytes and organic positive electrode (2, 5-dimethoxy-1, 4-benzoquinone (DMBQ)) were proposed. The charge-discharge performance of the batteries was investigated using a coin-type cell at 30˚C. The discharge capacity reaches ca. 200 mAh g(DMBQ) -1 in Mg(TFSA)2 /monoglyme and diglyme electrolytes. This capacity suggests that a multi-electron redox reaction takes place in these electrolytes. The hysteresis between charge-discharge voltage plateaus are quite large in Mg(TFSA)2 /diglyme, triglyme and tetraglyme electrolytes, while the discharge voltage increases drastically after a few cycles in Mg(TFSA)2 /monoglyme electrolyte. One of the reasons is that the overpotential of the Mg negative electrode for the Mg-dissolution is quite small. Although the capacity substantially decreases upon cycling, the cell using Mg(TFSA)2 /monoglyme retains the high voltage at the discharge even after 20 cycles.